“Programa de coaching educativo para mejorar el desempeño de los docentes de la I.E. N° 82572 de Cafetal, 2016” - Llanos Lozano, Aurelia Madeleine (2019)
ABSTRAC The purpose of the research was to determine the level of influence of educational coaching to improve the performance in the classroom of teachers of the I.E. N ° 82572 de Cafetal - Yonán in 2016. As a study methodology, the Pre Experimental design was used, applying the "Pre Test and Post Test with a single group". The population and study sample consisted of all the teachers of the primary level. The independent variable Educational Coaching Program and the dependent variable was Performance in the Teachers' Classroom. Taking as conclusion that in the Pre-Test analysis of teacher performance, it is observed of the 18 intervened, 7 (39 percent) indicate that there is a deficient level on a scale between 0 - 25 and with a score of 11 (61 percent) ) indicate that there is a regular level with a scale of 26 - 50 and after the application of the educational coaching program the data showed that 100 percent of the population indicates that the teaching performance is excellent, obtaining an average score of 63.72 with a variation of approximately 7.54 points in the IE N ° 82572 of Cafetal.